Evaluation of environmental sustainability of one-part geopolymer binder concrete - Kamal Neupane (Cleaner Materials, 2022)
Production of ordinary Portland cement (OPC) is a carbon-intensive process that generates significant amounts of carbon dioxide (CO2) gas from the combustion of fossil fuels and thermal decomposition of limestone. Overall, cement industries are responsible for around 7 % of global CO2 emissions which poses a considerable threat to global climate change because of its greenhouse effects. The recent advent of geopolymer shows great potential to reduce carbon footprints by utilizing the industrial by-products, such as fly ash and ground granulated blast furnace slag (GGBS) and convert into a binding material. Generally, geopolymer binders are made using aluminosilicate compounds (fly ash and or GGBS) and an alkali activator (combination of sodium silicate and sodium hydroxide solution) called “two-part geopolymer”. Despite having superior engineering properties to conventional OPC concrete, geopolymer concrete has not been widely adopted in concrete industry so far. The safety hazards in mixing and handling geopolymer concrete posed by sodium hydroxide is one of the barriers to the adaptation of geopolymer concrete. Replacing liquid sodium hydroxide with less hazardous alkali materials, such as sodium carbonate powder not only makes the geopolymer binder less hazardous and easier for mixing and handling process but also makes it more environmentally sustainable because of its lower embodied energy compared to sodium hydroxide. This study investigates the environmental sustainability of structural grades one-part geopolymer concrete and compares the results with OPC concrete of same strength grades. This investigation also includes a comparison between various types of geopolymer concrete of 40 MPa and 50 MPa grades produced in previous studies. This study found that one-part geopolymer binder concrete emits around 65 % less CO2 than OPC concrete of same strength grades, which is also 23 % less than geopolymer concrete of same strength grades produced in previous studies.